Sabal palmetto: Sabal or Cabbage Palm - Timothy K. Broschat (EDIS)
The sabal palm, or cabbage palm, is native to Florida and coastal regions of North and South Carolina and Georgia and is the state tree of both South Carolina and Florida. The name “cabbage palm” comes from its edible immature leaves, or “heart,” which has a cabbage-like flavor. This 5-page fact sheet was written by T. K. Broschat, and published by the UF Department of Environmental Horticulture, July 2013.